1984
DOI: 10.2320/matertrans1960.25.187
|View full text |Cite
|
Sign up to set email alerts
|

Volatilization of Aluminum Oxycarbides and of Alumina with Carbon in Reduction of Alumina

Abstract: The volatilization in the A1-O-C(-Si-Fe) system have been investigated mainly by thermal gravimetry in vacuum for four cases; (1) aluminum oxycarbides, (2) mixtures of alumina and carbon with and without additives (iron oxide, silicon nitride and silicon carbide), (3) mixtures of alumina and aluminum carbide or silicon carbide and (4) mixtures of alumina, silica (mullite), iron oxide and carbon. A12OC evaporated essentially congruently, whereas A14O4C evaporated incongruently; a -A12O3 was formed in addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In [8], the authors studied aluminum oxycarbides, mixtures of aluminum oxide with carbon, mixtures of aluminum oxide and aluminum carbide with silicon carbide, and mixtures of aluminum oxide with silicon dioxide and carbon. It was shown that Al 2 OC vaporizes congruently and Al 4 O 4 C vaporizes incongruently with the accumulation of aluminum oxide in the condensed phase.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…In [8], the authors studied aluminum oxycarbides, mixtures of aluminum oxide with carbon, mixtures of aluminum oxide and aluminum carbide with silicon carbide, and mixtures of aluminum oxide with silicon dioxide and carbon. It was shown that Al 2 OC vaporizes congruently and Al 4 O 4 C vaporizes incongruently with the accumulation of aluminum oxide in the condensed phase.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yokokawa et al [8] investigated the volatility of the components in the Al-O-C system (under vacuum) by thermogravimetric analysis. In [8], the authors studied aluminum oxycarbides, mixtures of aluminum oxide with carbon, mixtures of aluminum oxide and aluminum carbide with silicon carbide, and mixtures of aluminum oxide with silicon dioxide and carbon.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Journal of the Ceramic Society of Japan 100 [7] 1992 981 graphite did not proceed when two materials were placed separately in vacuum, while the reaction proceeded in Ar flows without their direct contact. According to Motzfeldt and Steinmo8), the reaction between separated Al2O3 and C proceeds through the following reactions; Al2O3(s)+4Al(g)=3Al2O(g), (2) 3Al2O(g)+3C(s)=6Al(g)+3CO(g).…”
mentioning
confidence: 99%